2019
DOI: 10.1108/ijoa-02-2019-1646
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated canvas on turnaround strategy

Abstract: Purpose The purpose of this study is to provide a comprehensive understanding regarding corporate turnaround. An integrated discussion regarding different corporate failure factors, conditions, symptoms followed by turnaround strategies and its results have been provided. Design/methodology/approach Authors have done a comprehensive systematic and integrated literature review study of research articles on corporate turnaround. The paper reviewed discussed different dimensions of turnaround management. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
(85 reference statements)
1
5
0
Order By: Relevance
“…Such an organizational with positive climate would manifest with major contribution from employees. The result of this research was in coherence with past studies (Bhattacharyya, 2019, 2021). Furthermore, it was also observed from this study findings that social enterprises were better poised to assimilate learning and apply organizational resources and capability to secure better economic gain.…”
Section: Discussionsupporting
confidence: 90%
“…Such an organizational with positive climate would manifest with major contribution from employees. The result of this research was in coherence with past studies (Bhattacharyya, 2019, 2021). Furthermore, it was also observed from this study findings that social enterprises were better poised to assimilate learning and apply organizational resources and capability to secure better economic gain.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, this study provided managerial inputs regarding the changed way of doing business required going into the future. This study was conducted in Indian urban market setting during COVID-19 unlock phase to arrive at an integrated understanding as a well-established practice in strategic management (Bhattacharyya, 2020c; Bhattacharyya & Malik, 2020). In future, studies could be conducted in rural areas of India to ascertain what ways rural shopkeepers undertook.…”
Section: Discussionmentioning
confidence: 99%
“…well-established practice in strategic management (Bhattacharyya, 2020c;Bhattacharyya & Malik, 2020). In future, studies could be conducted in rural areas of India to ascertain what ways rural shopkeepers undertook.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Specifically, an integrated perspective was much required. This was prescribed by the work of Bhattacharyya and Malik (2020). The study results indicated that managers had to 21 "Work performance trail of every team member could be measured, thus, a feedback system needs to built to provide employee insights" 22 "I feel it is very important that we take care of the mental health of our employees.…”
Section: Findings and Discussionmentioning
confidence: 99%